Pengaruh Kualitas Layanan, Fasilitas, Harga, Dan Lokasi Terhadap Kepuasan Konsumen Di Indo Futsal Kediri - Sastrawan, Andri; Marwanto, IGG Heru; Djunaedi, Djunaedi; Sustiyatik, Enni (Jurnal Ilmiah Raflesia Akuntansi, 2023)
This study aims to determine the influence of service quality, facilities, price, and location on consumer satisfaction at Indo Futsal Kediri. The type of research used is quantitative, a method that describes in detail the object of study. The population in this study consists of 960 visitors to Indo Futsal Kediri in June 2022, with a sample of 100 respondents. The sampling technique used is convenience/accidental sampling. Data collection methods include questionnaires, observation, documentation, and literature study. The data analysis methods used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial significance tests (t-test), simultaneous significance tests (f-test), and the coefficient of determination. The results of this study conclude that: (1) Service quality (X1), facilities (X2), price (X3), and location (X4) together (simultaneously) have a relationship with the dependent variable, which is consumer satisfaction (Y). (2) Service quality, when examined individually, does not have a significant relationship with the consumer satisfaction variable. This can be proven by the t-test result of -0.552, which is smaller than the t-table value of 0.677, with a significance level of 0.582, which is greater than 0.050.